1989
DOI: 10.1002/ijc.2910440327
|View full text |Cite
|
Sign up to set email alerts
|

Localization and imaging of radiolabelled monoclonal antibody against squamous‐cell carcinoma of the head and neck in tumor‐bearing nude mice

Abstract: Nude mice carrying human squamous-cell carcinoma xenografts were given i.v. injections of radiolabelled monoclonal antibodies (MAbs). MAb E 48, which reacts with squamous-cell carcinomas, was labelled with 131I, while a second control MAb of similar immunoglobulin subclass was labelled with 125I. Both antibodies were injected simultaneously, then the mice were scanned with a gamma camera or their tissues were removed and antibody uptake was calculated as a percentage of the injected dose. Uptake of E 48 reache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 11 publications
1
10
0
1
Order By: Relevance
“…Node-negative neck disease conventionally refers to clinically non-palpable neck nodes but this is a grossly inadequate and inaccurate method of identifying metastatic neck node [4,21,114,121,133]. Researchers have demonstrated that clinical N0 necks have shown occult metastases in about 30% or higher, depending on the size, site of primary tumor and the histological diagnostic methods [21,118].…”
Section: Diagnosing the Node-negative Neckmentioning
confidence: 99%
“…Node-negative neck disease conventionally refers to clinically non-palpable neck nodes but this is a grossly inadequate and inaccurate method of identifying metastatic neck node [4,21,114,121,133]. Researchers have demonstrated that clinical N0 necks have shown occult metastases in about 30% or higher, depending on the size, site of primary tumor and the histological diagnostic methods [21,118].…”
Section: Diagnosing the Node-negative Neckmentioning
confidence: 99%
“…MAb mouse E48 IgG 1 (Quak et al, 1989) is directed against an antigen present on squamous epithelial cells and their neoplastic counterparts. Both MAbs were kindly provided by Centocor (Leiden, The Netherlands).…”
Section: Reagents Mabs and Iodinationmentioning
confidence: 99%
“…Recently, we described the capacity of MAb E48 IgG for highly specific delivery of radioisotopes in nude mice carrying human head and neck SCC xenografts (Quak et al, 1989). However, F(ab')2 fragments have been demonstrated to have better tumour to non-tumour ratios in nude mice bearing xenografts due to a more rapid clearance from the blood (Pervez et al, 1988;Colapinto et al, 1988;Buchegger et al, 1986;Endo et al, 1988).…”
mentioning
confidence: 99%